A BIBLIOMETRIC ANALYSIS ON HAPPINESS USING VISUALIZATION - Paliwal, Divyany; Bhatnagar, Shivani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Happiness is a state of well-being characterized by feelings of joy, satisfaction, contentment, and fulfillment. It is both a fleeting emotion that arises from positive experiences and a deeper sense of life satisfaction and purpose. Happiness is influenced by various factors, including personal achievements, relationships, mindset, and the ability to find meaning in life. In this research, publications on "Happiness" between 2005 and 2025 in the Scopus and WOS database are examined. The bibliometric analysis technique was used in the study. As a result of the bibliometric analysis of 2892 articles evaluated, the following data were obtained: The year with the most written articles was 2021. It has been observed that there has been an increase in the number of articles since 2008. The four documents most cited were Ruggeri (2020), Blanchflower (2021b), Yang (2020) and Yõldõrõm (2021b) and the top four authors were found Rafael ravina-ripoll, David G. Blanchflower, Murat Yõldõrõm and Shigehiro Oishi. The top four publishing institutions are Springer, Elsevier Ltd, MDPI and Routledge. The four most cited countries are the United States, China, Spain and India,